Study on the Influence of Regional Transportation on PM2.5 Based on the RAMS-CMAQ Model in Weihai, a Typical Coastal City of Northern China - Wentao Ning; Zhiwen Xing; Min Wei; Mingyan Li; Meigen Zhang; Houfeng Liu (Aerosol and Air Quality Research)
Abstract Weihai, on the east coast of China, is the only city in Shandong Province that the air quality has reached the Chinese National Ambient Air Quality Class II Standard. However, heavy pollution events still occurred in winter and spring. In this study, the Integrated Source Apportionment Method (ISAM), a source analysis tool coupled with the Regional Atmospheric Modeling System and the Community Multiscale Air Quality modeling system (RAMS–CMAQ), was used to quantify the contribution of regional transport to PM2.5 and its main components in Weihai during February to March in 2018. The results showed that regional transport dominated PM2.5 pollution in Weihai, and the contributions of transport outside Weihai in February and March were 55.6–65.5% and 61.3–68.6%, respectively. Different components in PM2.5 showed the proportion of pollutants varies enormously. Secondary particles were mainly transported via long distances. The proportion of long-range transportation of nitrate had the highest value, and the contribution of regional transportation outside Weihai was 87.5–92.5% and 88.2–91.7%, followed by sulfate, which was 67.9–80.6% and 80.8–86.2%, and the proportion of ammonium salt is the lowest, contributed for 38.8–70.8% and 41.1–71.9% in February and March, respectively. Black carbon (BC), organic carbon (OC), and ions (ions here include chloride, sodium, magnesium, potassium, calcium, iron, aluminium, silicon, titanium, manganese, and other major nonspecific fine particles) were mainly influenced by short-range transportation and local emissions. The contributions of BC outside Weihai were 26.0–49.8% and 34.2–55.2%, the values for OC were 33.5–52.9% and 41.0–53.0%, those for ions were 37.8–49.9% and 44.1–54.4%, respectively. The trajectories indicate that PM2.5 pollution in Weihai is significantly affected by transport from Shandong Province, North China, Northeast China and other regions Thus, the improvement in air quality in Weihai requires strengthening interregional joint pollution prevention.